2021
DOI: 10.3390/children8040275
|View full text |Cite
|
Sign up to set email alerts
|

Use of Paclitaxel to Successfully Treat Children, Adolescents, and Young Adults with Kaposi Sarcoma in Southwestern Tanzania

Abstract: Treating Kaposi sarcoma (KS) in children, adolescents, and young adults (AYA) remains a challenge in low- and middle-income countries (LMIC) where chemotherapy options and availability are limited. We describe a retrospective cohort review of pediatric patients with KS treated with paclitaxel in Mbeya, Tanzania, between 1 March 2011 and 31 December 2019. Paclitaxel was given to patients who had KS relapse, a contraindication to bleomycin, vincristine, and doxorubicin (ABV), special circumstances in which a cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Despite the severity of their KS and HIV disease, 51% (26/51) survived. After observing high mortality rates in patients with stage 4 disease who were treated with BV chemotherapy in our previous study in Lilongwe (2-year OS of 11.8%) [15], we treated patients with stage 4 disease at both sites with up-front intensified chemotherapy (ABV) starting in 2012, and paclitaxel was used as salvage after failure of ABV and led to encouraging outcomes with minimal toxicity in Mbeya, Tanzania [27]. Despite the difficulty of treating paediatric patients with KS visceral disease in LMICs [16,36], in this cohort, 60% (6/10) of patients with GI involvement and 42% (10/24) of patients with pulmonary KS survived.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the severity of their KS and HIV disease, 51% (26/51) survived. After observing high mortality rates in patients with stage 4 disease who were treated with BV chemotherapy in our previous study in Lilongwe (2-year OS of 11.8%) [15], we treated patients with stage 4 disease at both sites with up-front intensified chemotherapy (ABV) starting in 2012, and paclitaxel was used as salvage after failure of ABV and led to encouraging outcomes with minimal toxicity in Mbeya, Tanzania [27]. Despite the difficulty of treating paediatric patients with KS visceral disease in LMICs [16,36], in this cohort, 60% (6/10) of patients with GI involvement and 42% (10/24) of patients with pulmonary KS survived.…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel has been shown to be well-tolerated and superior to BV in a large, multicentre prospective clinical trial in adult patients with moderate to severe KS treated in LMIC settings [37]. Positive outcomes have also been reported among small paediatric cohorts [17,27,36]. Future studies may consider evaluating paclitaxel as firstline treatment for all patients with stage 2 disease if available and not cost prohibitive-or at least as an option for treatment intensification for those who do not experience CR with BV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paclitaxel is highly effective in the treatment of recurrent childhood brain tumors and is becoming a prospective management option for pediatric tumors [ 42 ]. Another study demonstrated the effectiveness of paclitaxel treatment on children affected by Kaposi sarcoma [ 43 ]. Perez-Somarriba and colleagues observed a strong response with normalization of tumor markers in three patients showing relapsed intracranial NGGCT, after treatment with gemcitabine, paclitaxel, and oxaliplatin [ 44 ].…”
Section: Chemotherapy-induced Cardiotoxicity In Childrenmentioning
confidence: 99%
“…Currently, there are no universal treatment guidelines for pediatric KS. Treatment recommendations are extrapolated based on adult KS or small retrospective studies ( 19 22 ). Our limited knowledge about the molecular pathobiology of pediatric KS (HIV + and HIV) constitutes a gap in our knowledge that this study aims to close.…”
Section: Introductionmentioning
confidence: 99%